THE ROLE OF THE SOGDIANS IN HISTORICAL AND CULTURAL PROCESSES ON THE TERRITORY OF UZBEKISTAN (Universal International Scientific Journal, 2026)
This article examines the role of the Sogdians in shaping the political, economic, and cultural spheres of modern-day Uzbekistan. Particular attention is paid to archaeological finds, written sources, and material monuments reflecting the political, social, and economic life of the Sogdians. It analyzes the cultural ties of Sogdiana with neighboring regions, the role of this state in the development of the Great Silk Road, and its contribution to world civilization.
Keywords: Sogd, Uzbekistan, archeology, Great Silk Road, ancient cities, culture, trade, civilization.